Family and school context in school engagement (European Journal of Education and Psychology, 2018)
Family, peers and school are the three main contexts associated with school engagement. This study aims to analyze possible gender and age differences in these contextual variables and school engagement, as well as the relationship between the two. Participants were 1543 secondary school children aged between 12 and 18 years (M = 14.24; SD = 1.63). Of the total sample group, 728 (47.2%) were boys and 815 (52.8%) were girls. All completed the Family and Peer Support (FPS) scale, the Teachers’ Support scale of the Health Behaviour in School-aged Children (HBSC) questionnaire, and the School Engagement Measure (SEM). The results reveal significant differences between boys and girls, with girls scoring higher in perceived peer support and behavioral and emotional engagement. Younger respondents were also observed to score significantly higher for perceived support from parents and teachers, as well as for school engagement. Significant correlation indexes were observed between contextual variables, as well as between these variables and school engagement, although it was for support from teachers that the strongest correlation was found.